(untitled) (Jurnal Bahasa, 2006)
Since the picking of the Malay language as the national language of our nation, it has gone through rigorous developments, from its vo-cabulary, structure, grammar, and the like. Day by day the users of the language have increased tremendously. This is because now the users are not only the native users but also other non-native speakers like the Chinese, Indians, Iban, Kadazan, and others. In this kind of the situation, the issue of wrong usage of the language has become a pre-dominant problem. Although this issue has been discussed in many books, articles, forums, papers, talks, seminars, and colloquiums, but the issue of wrong usage is still rampant among the users of the lan-guage. Although users make all kind of errors, but this study focuses on the issue of wrong usage from the semantic point of view